PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ID EXPRESS LOGISTIK INDONESIA JAKARTA BARAT DIVISI WAREHOUSE PROCESSING - Revaldo Dwi Riadi; Suprapto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of leadership style and work motivation on employee performance at PT. ID Express Logistik Indonesia West Jakarta Warehouse Processing Division. The research method used is quantitative. The sampling technique used saturated samples totaling 52 employees. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test with SPSS version 26 application. Based on the results of the study, the determination coefficient value was 75% and the hypothesis test obtained t count> t table or (12.258> 2.009), this is also strengthened by a significant value of 0.000 <0.005. Thus Ho1 is rejected and Ha1 is accepted. This means that leadership style (X1) has a significant effect on employee performance at PT. ID Express Logistik Indonesia West Jakarta. Based on the determination coefficient value of 80.8% and the hypothesis test obtained t count> t table or (14.511> 2.009), this is also reinforced by a significant value of 0.000 <0.005. Thus Ho2 is rejected and Ha2 is accepted. This means that work motivation (X2) has a significant effect on employee performance at PT. ID Express Logistik Indonesia West Jakarta. Leadership style (X1) and work motivation (X2) simultaneously have a significant effect on employee performance with the regression equation Y = 2.880 + 0.299 X1 + 0.649 X2 + α. The determination coefficient value is 82.4% while the remaining 17.6% can be influenced by other factors. The hypothesis test obtained the calculated F value> F table or (114.470> 3.191), this is also reinforced by a probability significance of 0.000 <0.05. Thus Ho3 is rejected and Ha3 is accepted. This means that there is a significant simultaneous influence between leadership style and work motivation on employee performance at PT. ID Express Logistik Indonesia West Jakarta.